Surface Physicochemical and Structural Analysis of Functionalized Titanium Dioxide Films - Trino, Luciana D. [UNESP]; Bronze-Uhle, Erika S. [UNESP]; George, Anne; Mathew, Mathew T.; Lisboa-Filho, Paulo N. [UNESP] (Elsevier, 2018)
Titanium and its alloys are recognized as acceptable materials for many applications. The properties of titanium dioxide (TiO2) thin films are directly related to the structural characteristics of the material, which can be modified with tailor-made functional groups. Reactive bifunctional groups can be bound with hydroxyl-terminated TiO2, leading to the formation of self-assembled monolayers or multilayer films. The understanding of such interactions is necessary to design functional oxide coatings for a large variety of applications. In this study, nanosized TiO2 films were synthesized by the sol-gel method and deposited by spin coating technique upon titanium substrate. Subsequently, TiO2 thin films were functionalized with (3-aminopropyl)trimethoxysilane (APTMS), 3-(4-aminophenyl)propionic acid (APPA), 3-mercaptopropionic acid (MPA) or polyethylene glycol (PEG). Surface characterization by XPS, surface roughness, and contact angle indicated successful functionalization and allowed for identification of the preferential conformation of each molecule. APPA and APTMS presented free amine groups indicating the attachment to the surface by carboxyl and silane groups, respectively. Mercapto coupling from MPA showed the formation of S-Ti bonds. PEG-coated surface revealed polymerization of several hydroxyl groups that crosslinked with each other. Analyzing the mode of attachment at the interface of the metal oxide and functional group may help in the development of improved functional materials.
Keywords: adhesion mode; functional materials; functionalization; physicochemical properties; thin films; titanium dioxide